2011
DOI: 10.1063/1.3557067
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing and activating dopants in ⟨112⟩ silicon nanowires by alkene adsorptions: A first-principles study

Abstract: The B dopant stability and doping level tunability of ͗112͘ silicon nanowires ͑SiNWs͒ with alkene adsorption are revealed based on first-principles calculations. It is found that the alkenyl chains favor the middle location of ͑111͒ facet, and the B dopants prefer to locate at ͑110͒ facet of the ͗112͘ SiNW. Interestingly, the B doping levels are activated upon an alkene adsorption which introduces an intermediate energy level. This finding sheds light on how SiNWs can achieve effective doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…-The thermal transport properties of Si nanowires (SiNWs) have drawn significant attention recently because of their important role in applications such as nanoelectronics and thermoelectrics [1,2]. Due to their significant size and surface dependences [3][4][5], they can be effectively tuned by changing the surface-to-volume ratio of SiNWs. It has been found that surface functionalization may enhance phonon scatterings at the surface/boundary of nanostructures and thus cause thermal conductivity reduction [5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…-The thermal transport properties of Si nanowires (SiNWs) have drawn significant attention recently because of their important role in applications such as nanoelectronics and thermoelectrics [1,2]. Due to their significant size and surface dependences [3][4][5], they can be effectively tuned by changing the surface-to-volume ratio of SiNWs. It has been found that surface functionalization may enhance phonon scatterings at the surface/boundary of nanostructures and thus cause thermal conductivity reduction [5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…At the same time, a great research effort has been directed toward the electronic and thermal transport properties of silicon nanostructures to explore thermoelectric-related applications, where low thermal but high electronic conductivity of materials is required to obtain high thermoelectric efficiency. Our previous theoretical studies [1,2,[9][10][11][12] revealed that surface passivation and strain engineering can effectively tune the electronic band structure of silicon nanowires (SiNWs) and SiNSs; remarkable surface-transfer doping is also found in SiNWs. In addition, the thermal conductivity of SiNWs has been extensively studied both experimentally [13,14] and theoretically [15][16][17][18].…”
mentioning
confidence: 99%
“…Firstprinciples calculations on nitrogen atoms adsorbed on the (110) facets of SiNWs revealed the formation of N-Si-N-Si chains, sequentially inducing metallization [30]. Recent theoretical and experimental investigations have demonstrated an effective doping of SiNWs induced by electron transfer across the surface layer, which contributes a considerable concentration of majority carriers to SiNWs with surface passivants [31,32].…”
mentioning
confidence: 99%